Novel Algorithm Based Upon Reinforcement Learning to Better Improve Energy Consumption in WSN - Soni, Santosh; Shivastava, Manish (International Journal of Computer Sciences and Engineering, 2025)
Nowadays, Wireless sensor network is highly potential area in various sectors like industry, research, medical, education and IOT. Sensor nodes are generally equipped with tiny battery to perform various operations. The key area is to save energy consumption of WSN node. In this research study, we have proposed a novel algorithm to better improve the energy optimization using reinforcement learning. The reinforcement learning technique is based upon state, action, policy and certain learning and discount factors. We have simulated the proposed algorithm in mat lab and compared the findings with state of the art algorithm like RL-CRC [26] to better improve energy consumption and other performance parameters.